Factors that Influence People to Buy Clothes Onlıne - Radhey Grover (International Journal of Advanced Science and Technology, 2020)
Clothing is the vital need of every individual on this planet. The apparel industry reworks on people’s living styles alongside their social and money standing. Adding to it is the emergence of the online shopping world that is no less than a blessing to any ordinary citizen in this world. With websites like Myntra, Jabong, SHEIN, AJIO etc. coming into existence, they’re attracting major chunk of people across the globe. Further leading to significantly causing an impact in the landscape of the Indian  Market. The major contribution in shaping the  retail market is done by the Gen Y.After the availability of clothes sold online a lot of things changed as it gave an option to sit at home and select and compare the best of what anyone wants to be ordered at the doorstep. This phenomenon has created a turbulence in the clothing industry as conventionally people used to visit their favourite shops and brand showrooms for their clothes but now everything, they desire is available on a single platform.It has been written to to understand in depth on  factors that persuades people to buy them online . This study includes the empirical and quantitative data to analyse the same and the methodology used is correlation and linear regression using SPSS 18.0.After conducting the detailed analysis, the findings concluded that the purchasing intention of the buyer has a relation to the internet shopping attitudes.